Maxwell–Wagner Polarization and Mixed Ferromagnetic and Antiferromagnetic State in Eu2CoMnO6 - Alam M.; Kumar D.; Kumar S.; Sawada M.; Shimada K.; Chatterjee S. (My University, 2025)
Herein, the electrical and magnetic properties of polycrystalline Eu2CoMnO6 are explored. More specifically, based on transport, dielectric, and impedance measurements, a thermally activated dielectric polarization near room temperature is reported. The valence states of transition metals in the Eu2CoMnO6 sample are studied by measuring the X-ray absorption spectra at both Co-L2,3 and Mn-L2,3 edges. Moreover, based on magnetization, X-ray absorption spectroscopy, and X-ray magnetic circular dichroism measurements, the coexistence of competing ferromagnetic and antiferromagnetic phases is probed. Dielectric measurement shows a large dielectric constant near room temperature along with a large frequency dispersion. The temperature-dependent resistivity, Cole–Cole plot, and imaginary part of impedance confirm the semiconducting nature of Eu2CoMnO6. Temperature-dependent magnetization shows a second-order magnetic transition below 125 K. Isothermal magnetization versus magnetic field loop shows first-order metamagnetic transition, driven by mixed magnetic state owing to the presence of antisite disorder and antiphase boundary. © 2023 Wiley-VCH GmbH.